Units against Flagrante Delicto in Peru: Some notes on their necessity and usefulness - Machuca Fuentes, Carlos Espirito (2022)
In Trujillo, northern Peru, the Units against Flagrante Delicto has been recently (July, 2022) inaugurated within the so-called Integrated Center of the Judicial Administration System, in which the Judiciary and the Government Attorney General’s Office stand out, in small and unified environments. The need for solutions to opportunely deal with cases where the perpetrator of a crime is apprehended almost instantaneously or within the legal assumptions of the so-called «in flagrante delicto» has resulted in the implementation of environments such as the above mentioned, especially in places with high crime rates. Are these mechanisms effective in reducing crime? In the following lines we will try to reach some explanations.